Structural Equation Modeling of Educational Use of Facebook among University Students in Pakistan (Journal of Social Sciences Review, 2022)
South Asia, the world's most populous region, has the highest number of young social networking site users. Pakistan has over 40 million young active Facebook users among them. As a result, there is a greater need to explain how young people, particularly students, can use social networking sites like Facebook for educational purposes. The purpose of this paper is to investigate Pakistani students' attitudes, perceptions, and behavior toward Facebook, as well as how they use the platform for learning purposes. The researchers conducted a cross-sectional survey at three Pakistani universities. The study included a sample of 1050 students who were Facebook users and were selected randomly. We developed a structural equational model to outline the relationships between different types of independent and dependent variables. We used appropriate fitting indices such as the goodness of fit index (GFI), comparative fit index (CFI), and non-normal fit index (NFI) to test our model. The proposed model's results confirmed the hypothesized latent structures as well as the theoretical validity of the probed factors. The study's findings may be useful in better understanding the educational use of social networking tools in Asian and non-western countries.
Keywords: Social Network; Adoption; Diffusion of Innovation; Facebook; Educational Context